Technological Innovation and Agrifood Systems Resilience: The Potential and Perils of Three Different Strategies - Charatsari, Chrysanthi; Lioutas, Evagelos D.; De Rosa, Marcello; Vecchio, Yari (Frontiers in Sustainable Food Systems, 2022)
The interest in technological innovation has burgeoned in recent years. Theory and research support the vital role of innovative technologies in enhancing agrifood systems resilience. In this theoretical contribution, focusing on different sets of technologies, we present three technological innovation strategies, discuss their potential for strengthening resilience, and expose some open issues that need to be addressed. Responsible technological innovation arose as a response to the growing concerns about the possible unintended impacts of mega-technological trends, like digital farming tools or nanotechnologies, on agrifood systems. Although responsibly innovating is far from easy, and despite the gaps between theoretical ideals and innovation praxis, responsible technological innovation is a promising development since it can prevent counterintuitive effects of technologies on resilience. On the other hand, poly-innovation emerged as a social practice in which internetworking technologies facilitate—and create bundles with—organizational, social, and business innovation. In that strategy, technology represents a mediator of resilience-enhancing social behavior. However, by promoting the uberization of agrifood systems, poly-innovation is associated with various uncertainties. Finally, micro-innovation refers to the incremental adaptations of existing technologies or the development of new ones through bricolage and tinkering. The commercialization of such innovations through open design can increase the resilience of small-scale farming, especially in low-income countries. Nonetheless, the lack of financial resources, technical assistance, and institutional support hamper the full exploitation of micro-innovation.